2018
DOI: 10.1371/journal.pone.0196431
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in the planktonic cnidarian community in a mesoscale area of the NW Mediterranean

Abstract: In the present work, possible long-term changes in the planktonic cnidarian community were investigated by analyzing (1) species and community spatial distribution patterns, (2) variations in abundance and (3) changes in species richness during three mesoscale surveys representative of the climatic and anthropogenic changes that have occurred during the last three decades (years: 1983, 2004 and 2011) in the NW Mediterranean. These surveys were conducted during the summer (June) along the Catalan coast. All sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Considering that our study area is mostly coastal, it is not surprising that the highest diversities were found in coastal environments and, consequently, were mainly associated with the contribution of meroplanktonic hydromedusan species (particularly those belonging to Anthoathecata and Leptothecata orders) [38]. This result is in accordance with hydromedusan patterns observed in coastal ecosystems at different latitudes worldwide [10,41,45,8589]. The hydrological dynamics and geomorphology of coastal environments would favor the development of hydromedusan species with benthic phases because costs are usually associated to retentive processes, which may favor reproductive encounters, and provide a wide offer of substrata, which enhances the probability of polyp settlement and success (see [66,90]).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Considering that our study area is mostly coastal, it is not surprising that the highest diversities were found in coastal environments and, consequently, were mainly associated with the contribution of meroplanktonic hydromedusan species (particularly those belonging to Anthoathecata and Leptothecata orders) [38]. This result is in accordance with hydromedusan patterns observed in coastal ecosystems at different latitudes worldwide [10,41,45,8589]. The hydrological dynamics and geomorphology of coastal environments would favor the development of hydromedusan species with benthic phases because costs are usually associated to retentive processes, which may favor reproductive encounters, and provide a wide offer of substrata, which enhances the probability of polyp settlement and success (see [66,90]).…”
Section: Discussionsupporting
confidence: 81%
“…tetraphylla in El Rincón region and massive accumulations in recent years reveal that its abundance distribution is expanding southwards [50]. Changes in the latitudinal distribution and abundance patterns of the species are one of the signals of climate warming, and warm-water species abundances would be positively favored [10,19,51,52]. Indeed, rising temperatures and drier conditions have been recorded in the Bahía Blanca Estuary affecting the plankton communities (i.e., producing changes in phenology and composition) via alterations of the water chemistry and predator-prey interactions [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to trophic limitation of fish larvae, changes in plankton composition and abundance may have important effects on the condition of juvenile and adult fishes, determining demographic parameters such as reproduction, growth, and mortality, and these changes have been proposed as important drivers of small pelagic population variability in the NW Mediterranean (Brosset et al, ; Coll et al, ; Saraux et al, ). Another indirect factor related to changing plankton dynamics is the increasing abundance and changes in gelatinous plankton composition that have been recorded in the NW Mediterranean (Guerrero, Gili, Grinyó, Raya, & Sabatés, ; Molinero et al, ). Jellyfish, specifically scyphozoan medusae, may negatively affect pelagic fish due to competition for food or through direct predation on their fish eggs and larvae (Purcell & Arai, ).…”
Section: Discussionmentioning
confidence: 99%
“…Spatiotemporal changes in egg and larval abundance can be a sensitive indicator of environmental change. The predicted increase in water temperatures, lower wind stress and precipitation, and the consequently higher stratification have reported to drive changes in the composition and phenology of planktonic communities (moLInero et al, 2005; and to increase the population size of gelatinous carnivores (moLInero, 2008;guerrero et al, 2018). Jellyfish, specifically scyphozoan medusae, may negatively affect fish due to competition for food or through direct predation on their fish eggs and larvae (purceLL & araI, 2001).…”
Section: The Mediterranean Under Climate Changementioning
confidence: 99%